2021
DOI: 10.3892/mmr.2021.12475
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation reduces cardiac pain through microglial deactivation in rats with chronic myocardial ischemia

Abstract: Angina pectoris is cardiac pain that is a common clinical symptom often resulting from myocardial ischemia. Spinal cord stimulation (SCS) is effective in treating refractory angina pectoris, but its underlying mechanisms have not been fully elucidated. The spinal dorsal horn is the first region of the central nervous system that receives nociceptive information; it is also the target of SCS. In the spinal cord, glial (astrocytes and microglia) activation is involved in the initiation and persistence of chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“… 15 , 16 Another study showed that SCS reduces chronic cardiac pain partially by inhibiting spinal microglial activation and, thus, potentially downregulates the expression of proinflammatory mediators, such as IL-1β and TNF-α. 30 Moreover, other studies showed that SCS might reduce microglial activation at the level of the spinal cord. 13 , 16 , 20 It is notable that our findings are contrary to results from a recent study showing that conventional SCS exacerbated microglial activation in the lumbar cord of CCI rats during the maintenance phase of NP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 , 16 Another study showed that SCS reduces chronic cardiac pain partially by inhibiting spinal microglial activation and, thus, potentially downregulates the expression of proinflammatory mediators, such as IL-1β and TNF-α. 30 Moreover, other studies showed that SCS might reduce microglial activation at the level of the spinal cord. 13 , 16 , 20 It is notable that our findings are contrary to results from a recent study showing that conventional SCS exacerbated microglial activation in the lumbar cord of CCI rats during the maintenance phase of NP.…”
Section: Discussionmentioning
confidence: 99%
“…Activation and CSF1 Levels in CCI Model Spinal Cord Despite that SCS could not normalize the PWT, it caused a significant increase in PWT, indicating that SCS is able to produce analgesic effects in CCI rats. Previous studies reported that a small but significant reduction in mechanical hypersensitivity could persist for up to 5 days in CCI rats even after the cessation of SCS, 26,[28][29][30] thus, this cannot be completely explained by GCT alone. Our study demonstrated that repeated SCS attenuated microglial activation, as indicated by reduced immunoreactivity of CD11b in the ipsilateral DH in CCI rats, is in agreement with results of previous studies showing that continuous SCS treatment for 4 days relieved NP by inhibiting activation of microglia and astrocytes in the spinal cord of rats with spared nerve injury.…”
Section: Scs Produces Analgesia By Inhibiting Microglialmentioning
confidence: 92%
“…For this purpose, methods of magnetic and electrical stimulation of the central nervous system are widely used. Electrical stimulation of the central and peripheral parts of the nervous system (stimulation of the structures of the autonomic nervous system, epidural electrical stimulation of the spinal cord, electrical stimulation of individual nerves and nerve bundles) has now found wide application and has shown high efficiency in clinical practice for the functional correction of many neurological and neurosurgical diseases, such as Parkinson's disease, essential tremor, epilepsy, spastic and pain syndromes (6,11,13,31). Considering the high frequency of concomitant "age-related" diseases accompanied by chronic pain syndromes, we conducted a study to identify possible positive effects of electrical spinal cord stimulation in elderly patients with chronic cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The high social significance and prevalence of these disorders determines the relevance of finding new ways to correct these conditions, however, existing pharmacological methods that improve the functional state of the central nervous system (CNS) do not always meet the expectations of both doctors and patients (3,4). In recent years, various methods of neuromodulation based on epidural electrical stimulation of the spinal cord have been proposed in clinical practice for the correction of peripheral hemodynamic disorders in patients suffering from refractory angina pectoris or peripheral vasculopathy (6)(7)(8)(9)(10)(11). Also, in many experimental and clinical studies, a positive effect of electrical stimulation of the spinal cord on the hemodynamic and functional parameters of the brain was noted in certain pathological conditions associated with dysfunction of the vascular bed, such as ischemia, subarachnoid hemorrhage, head trauma and brain tumors (10,(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…This study suggests that SCS exhibits anti-inflammatory effects ( 24 ). Moreover, Wang et al ( 25 ) reported the ability of SCS to decrease spinal neuroinflammation induced by cardiac myocardial infarction in rats. This effect is achieved by inhibiting spinal microglial p38 in the mitogen-activated protein kinase pathway (MAPK), which subsequently reduces the levels of proinflammatory mediators IL-1β and TNF-α in the spinal cord.…”
Section: Literature Reviewmentioning
confidence: 99%